Dexmedetomidine dosage in critically ill patients undergoing intraoperative wake-up test: A randomized controlled trial. Issue 10 (11th March 2022) - Yang, Ting; Mudabbar, Muhammad Saqib; Chen, Tao; Jia, Hong; Fu, Qiang; Liu, Bin
Abstract: Objective: The aim of this study was to find the optimum dosage of dexmedetomidine in Spinal Orthopedic Scoliosis Correction Surgery when used in combination with propofol and remifentanil in American Society of Anesthesiologists (ASA) III patients with severe scoliosis undergoing intraoperative wake-up test. Materials and methods: We selected a total of 60 ASA III ⩽40 years old patients who underwent Spinal Orthopedic Scoliosis Correction Surgery (SOSCS) and randomized them into groups A, B, and C. Group A was administered 0.2 μg/(kg·h) of dexmedetomidine, group B 0.3 μg/(kg·h), and group C 0.4 μg/(kg·h). The main parameters monitored were: wake-up time; wake-up quality; adverse effects that occur while the patient is awake; postoperative awareness of intraoperative wake-up test; heart rate (HR); mean arterial pressure (MAP); and oxygen saturation (SpO2 ). Values of these parameters were monitored at 7 timestamps separated by 5 minutes >30 minutes. Results: Group B had a higher MAP at 10 minutes before wake-up ( P  = .03) and at the moment of wake-up ( P  = .04) than group A. The Wake-up time of group A was 14.95 ± 7.42 minutes, group B was 14.7 ± 6.52 minutes, which was significantly shorter than that of group C 21.3 ± 10.02 minutes ( P  = .02). The wake-up quality was excellent. All other parameters had no significant statistical differences. Conclusion: Doses of 0.2 to 0.3 μg/(kg·h) have shorter wake-up time and fewer hemodynamic fluctuations compared to 0.4 μg/(kg·h).